(untitled) (Research, Society and Development, 2020)
The Council of Health (CoH) are privileged instances for social participation through political representation, given its deliberative character. However, there are numerous scientific evidences that show difficulties in the exercise of councilor representation. The objective of this paper is to comprehend the notion of political representation that leads the activities of councilors. It is a case study, conducted by semi-structured interviews with the members of the City Council of Health, Viçosa, Minas Gerais, from April through June of 2012. The testimonials were analyzed through "Thematical Analysis", according to the procedure proposed by Bardin (2008). The results show a distancing from the theoretical assumptions of political representation, revealing occasions of defense of private interests over community interests; lack of knowledge and/or omission from demands of the representation bases; incipient articulation with them. It has been observed that the instruments and mechanisms of accountability, responsible for sanctions in the traditional system of parliamentary political representation, proved inadequate for the reality of CoH, compromising the integrality of the political representation and, therefore, the social participation in the CoH.